Mutational analysis of PHEX gene in X-linked hypophosphatemia. - Dixon, P; Christie, P; Wooding, C; Trump, D; Grieff, M; Holm, I; Gertner, J; Schmidtke, J; Shah, B; Shaw, N; Smith, C; Tau, C; et al. (1998)
Hypophosphatemic rickets is commonly an X-linked dominant disorder (XLH or HYP) associated with a renal tubular defect in phosphate transport and bone deformities. The XLH gene, referred to as PHEX, or formerly as PEX (phosphate regulating gene with homologies to endopeptidases on the X-chromosome), encodes a 749-amino acid protein that putatively consists of an intracellular, transmembrane, and extracellular domain. PHEX mutations have been observed in XLH patients, and we have undertaken studies to characterize such mutations in 46 unrelated XLH kindreds and 22 unrelated patients with nonfamilial XLH by single stranded conformational polymorphism and DNA sequence analysis. We identified 31 mutations (7 nonsense, 6 deletions, 2 deletional insertions, 1 duplication, 2 insertions, 4 splice site, 8 missense, and 1 within the 5' untranslated region), of which 30 were scattered throughout the putative extracellular domain, together with 6 polymorphisms that had heterozygosity frequencies ranging from less than 1% to 43%. Single stranded conformational polymorphism was found to detect more than 60% of these mutations. Over 20% of the mutations were observed in nonfamilial XLH patients, who represented de novo occurrences of PHEX mutations. The unique point mutation (a-->g) of the 5'untranslated region together with the other mutations indicates that the dominant XLH phenotype is unlikely to be explained by haplo-insufficiency or a dominant negative effect.